PENTINGNYA UPAYA MENINGKATKAN MINAT BELAJAR IPS DENGAN MENGGUNAKAN MEDIA AUDIO-VISUAL PADA SISWA - Ainal Fitra; Annisa Nur Fadilah (Jurnal Pendidikan dan Pembelajaran, 2024)
The aim of this research is to determine the extent to which learning activities using audio-visual media increase interest in learning social studies. Local facts show that when studying social studies, students are more self-centered, do not pay attention to teachers and are indifferent to other friends. This shows that students' interest in social studies is still low. Audio-visual media is expected to increase interest in learning social studies because the application of audio-visual media can increase. So that students' character can change habits and care about the environment. The research method uses quantitative research methods, which are carried out by searching for material in written form. The aim of this research is to increase interest in learning social studies through audio-visual media. The results of this research indicate that the use of audio-visual media is very important to increase elementary school students' interest in learning social studies.